Protein molecular defect detection method based on a neural network algorithm - Zheng, Meiqing; Kahrizi, Somayeh (Cellular and Molecular Biology, 2020)
Proteins, as the largest macromolecules in the body, are among the most important components of the body and play very vital and important roles. These substances are made up of a series of amino acid chains that, depending on the type of protein, the number of these amino acids can reach several thousand. Proteins function differently depending on the type and location of their presence, including enzymatic activity to catalyze the process, identify microbes and cancer cells, transport substances such as respiratory gases, and signalize. In the biochemical experiment, the problem of optimizing the detection of protein molecular defects, because of the randomness of the information, parameters, selection and setting, limits the detection accuracy of protein molecular defects. Based on the characteristics of fast learning speed and a robust network of neural network algorithm, a protein molecular defect detection method based on a neural network algorithm was proposed. Firstly, the protein secondary structure was predicted by the method of protein secondary structure prediction based on the generalized regression neural network to obtain the protein structural features; secondly, the protein defective molecular sequence classification model based on the neural network was used to classify the protein defective molecular sequence to achieve the protein molecular defect detection. The results showed that the detection accuracy of the proposed method was very high, which meets the needs of protein molecular defect detection, and has some application advantages compared with similar detection methods.